Pengaruh Tata Ruang Interior Studio Kreatif terhadap Produktivitas Pelaku Desain - Heru Subiyantoro; Sarah Putri Nurhaliza (Universitas Muhammadiyah Palembang, 2026)
The physical work environment plays a crucial role in supporting the productivity and well-being of creative industry professionals, particularly designers. This study aims to analyze how interior spatial elements namely color, material, lighting, and circulation affect designers’ productivity in creative studios. Employing a descriptive quantitative approach, data were collected through online questionnaires distributed to graphic designers, architects, and product designers working in various studios across Indonesia. The findings reveal that interior elements significantly influence comfort, focus, and interaction within the workspace. Neutral colors support concentration, natural materials such as wood enhance the comfort of the space, adaptive lighting facilitates a healthy work rhythm, and efficient space circulation helps facilitate interaction and teamwork. These findings highlight the importance of designing studio interiors that are not only aesthetically pleasing but also responsive to the psychological and ergonomic needs of users. This research is expected to serve as a reference in designing productive and human-centered creative workspaces.